Using Latin America as a research laboratory: The moderating effect of trade openness on the relationship between inward and outward FDI. Issue 2 (15th July 2019) - Borda Reyes, Armando; Newburry, William; Carneiro, Jorge; Cordova, Carlos
Abstract : Purpose: This paper aims to use Latin America as a laboratory to better understand the relationship between inward foreign direct investment (IFDI) and outward foreign direct investment (OFDI) (both in total as well as in regional flows) and also examine the moderating effect of trade openness on that relationship. Latin America is an ideal study context for this purpose because of the relative homogeneity of its countries, which reduces confounding effects and increases comparability. Design/methodology/approach: This paper uses longitudinal panel regression models with moderation effects. Secondary data were gathered on IFDI (per country and per country-sector), OFDI (total per country and region-targeted per country) and on trade openness from 11 Latin American countries. Findings: IFDI in natural resources is positively associated with OFDI in both overall total flows and regional flows. The effect of IFDI in manufacturing has a consistent negative effect on total OFDI. IFDI in services has positive effects on total OFDI. Additionally, trade openness moderates positively the relationship between total IFDI and both total OFDI and regional OFDI. As a consequence, the authors found evidence suggesting that the relation between IFDI and OFDI in Latin America is positively moderated by trade openness. Originality/value: The authors explored the nature of the impact of IFDI on the capacity of the recipient country to compete abroad as expressed by its OFDI flows. Specifically, they elucidated whether trade openness can be considered a suitable mechanism for home country firms to leverage potential spillovers provided by foreign entrants.